De novo synthesis of multisubstituted aryl amines using alkene cross metathesis. - Tatton, MR; Simpson, I; Donohoe, T (2014)
The olefin cross-metathesis reaction allows rapid access to 1,5-dicarbonyl intermediates which, upon treatment with a primary or secondary amine, allow the synthesis of a range of multisubstituted carbocyclic aryl amines. This de novo arene synthesis yields nonclassical substitution patterns in a regioselective and predictable approach that is compatible with several functional groups.